COMPARATIVE ANALYSIS OF SERVICE PERFORMANCE BETWEEN PHNOM PENH'S AND TRANSJAKARTA CITY BUSES - Sri Setia Lestari; Jovinda Raffael D.F; M. Farhan Ahmadani; Amelia Dwi Alviani; Roselina Rahmawati; Nadila Mutiara Faeza; Rachadyan Narotama; Vannia Ardelia Amanda (Journal Innovation of Civil Engineering (JICE), 2024)
The cities of Jakarta and Phnom Penh face the same traffic problems, namely traffic congestion caused by the high number of private vehicle owners in both regions. To get around the problem, public transportation such as TransJakarta and Phnom Penh City Bus are used. The puIDRose of this study is to compare the performance of TransJakarta and Phnom Penh City Bus public transportation systems. The approach used in this research is a qualitative approach by comparing the same variables from both case studies. The comparison between TransJakarta and Phnom Penh City Bus public transportation services shows differences in several aspects. The results show that TransJakarta has lower fares, dedicated lanes that reduce congestion, as well as a cashless payment system that increases user convenience. In contrast, Phnom Penh City Bus faces challenges such as higher fares, lack of dedicated lanes, and reliance on cash payments, which hinder its operational efficiency. The contribution of this research emphasizes the importance of applying best practices from TransJakarta in global public transport management, such as the development of user-friendly infrastructure, improved accessibility, and the use of modern technology for payment systems. The findings will provide insights for policy and transport managers in various countries to design a more efficient public transportation system. Keywords: Public Transportation; TransJakarta; Phnom Penh City Bus.